2018
DOI: 10.1096/fj.201800354
|View full text |Cite
|
Sign up to set email alerts
|

Topical application of anthranilate derivatives ameliorates psoriatic inflammation in a mouse model by inhibiting keratinocyte‐derived chemokine expression and neutrophil infiltration

Abstract: Psoriasis is an inflammatory autoimmune skin disorder possessing a complex etiology related to genetic and environmental triggers. Keratinocytes show a potential role for the origin of psoriasis. In this study, we estimated the efficiency of 2 anthranilate derivatives-(E)-4-( N-{2-[1-(hydroxyimino)ethyl]phenyl}sulfamoyl)phenyl pivalate (HFP031) and butyl 2-[2-(2-fluorophenyl)acetamido]benzoate (HFP034)-on psoriasis amelioration in a mouse model. The results showed that topical treatment with both compounds cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 50 publications
3
21
0
Order By: Relevance
“…In the imiquimod-induced mouse psoriasis model, topical application of HFP034 could ameliorate the skin lesions and epidermal thickness via inhibition of inflammatory cytokines and chemokines and infiltration of neutrophils. Further investigations suggested that HFP034 increased the skin concentration of cAMP and inhibited the NF-κB activity (Lin et al, 2018 ). These results indicate that topical application of HFP034 tends to be a potential therapeutic option for psoriasis patients.…”
Section: Pde4 Inhibitors Under Development For the Treatment Of Inflamentioning
confidence: 99%
“…In the imiquimod-induced mouse psoriasis model, topical application of HFP034 could ameliorate the skin lesions and epidermal thickness via inhibition of inflammatory cytokines and chemokines and infiltration of neutrophils. Further investigations suggested that HFP034 increased the skin concentration of cAMP and inhibited the NF-κB activity (Lin et al, 2018 ). These results indicate that topical application of HFP034 tends to be a potential therapeutic option for psoriasis patients.…”
Section: Pde4 Inhibitors Under Development For the Treatment Of Inflamentioning
confidence: 99%
“…The skin samples were fixed in 10% formalin buffered in phosphate saline for immunohistochemical staining. The detailed procedure was described in the previous study 49 . The skin sections were incubated with anti-IL-6 antibody, anti-IL-17A antibody, anti-Ki67 antibody, and anti-Ly6G antibody for 1 h, and subsequently incubated with biotinylated donkey anti-goat IgG for 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…The levels of interleukin (IL)-6, chemokine (C-C motif) ligand (CCL)5, and CCL17 were measured using commercial kits (ELISA MAX Deluxe Set, BioLegend) based on the manufacturer’s instructions. The detailed procedures for the ELISA assay were described in our previous study (Lin et al, 2018).…”
Section: Methodsmentioning
confidence: 99%